VI International Scientific-Practical Conference “Social dynamics of population and human potential” - T. A. Ignatova (RUDN journal of Sociology)
The article presents an overview of the VI International Scientific-Practical Conference “Social dynamics of population and human potential” held on June 20-21 by the Institute of Socio-Economic Studies of Population of the FCTAS RAS with the support of the Department of Social Sciences of the RAS, Research Institute for Healthcare Organization and Medical Management, Research Institute on Issues of Socio-Economic Statistics of the Federal State Statistics Service, Vologda Scientific Centre of the RAS, and the Department of Sociology of Family and Demography of the Moscow State University. The plenary session covered a wide range of issues and various aspects of human potential and social problems, including mobility in different types of cities, national development goals, poverty, population decline and stratification, and the impact of state support on childbirth. Students and teachers of the RUDN University made presentations at the conference: at the thematic sections, they considered religious values in the contemporary Russian society and issues of national identity; the role of gentrification and its different aspects, and healthy lifestyle components; the urgent issues of sociology of management such as the role of Mendelian manager in organizational adaptation. The round table focused on the potential of artificial intelligence and its risks, especially in education, and some conclusions were made, including the low level of commitment to healthy lifestyles, the need to create equal conditions for all city dwellers, and negative effects of artificial intelligence on critical thinking.